2008
DOI: 10.1002/jpln.200625231
|View full text |Cite
|
Sign up to set email alerts
|

Silicon fractions in Histosols and Gleysols of a temperate grassland site

Abstract: The importance of silicon (Si) in nutrition is currently being recognized by its beneficial effects on many crops. Therefore, it is important to determine the soil Si status and to examine different extractants for testing plant-available Si. Little information is available about the Si status of Histosols and C org -rich Gleysols in temperate climate. This study was undertaken (1) to characterize different Si pools in C org -rich groundwater soils of an experimental site and (2) to study the influences of sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…The weakest extractant (after water) is CaCl 2 , which only extracts this easily soluble Si pool (Berthelsen et al, 2001). In our measurements, 2 g of dried soil (<2 mm) was shaken (linear movement) for 16 h with 20 ml 0.01 M CaCl 2 extractant (1:10 ratio) in a 50 ml Nalgene tube at 20 • C (Höhn et al, 2008). After centrifugation at 4000 rpm for 30 min, the supernatant was filtered over 0.45 µm pore size (Chromafil ® A-45/25) and analyzed for Si by the automated molybdate-blue method.…”
Section: Cacl 2 -Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The weakest extractant (after water) is CaCl 2 , which only extracts this easily soluble Si pool (Berthelsen et al, 2001). In our measurements, 2 g of dried soil (<2 mm) was shaken (linear movement) for 16 h with 20 ml 0.01 M CaCl 2 extractant (1:10 ratio) in a 50 ml Nalgene tube at 20 • C (Höhn et al, 2008). After centrifugation at 4000 rpm for 30 min, the supernatant was filtered over 0.45 µm pore size (Chromafil ® A-45/25) and analyzed for Si by the automated molybdate-blue method.…”
Section: Cacl 2 -Extractionmentioning
confidence: 99%
“…Solubility is a function of temperature, particle size, pH, chemical composition (type of Al and Fe oxides), organic matter (OM) content and exposed surface area Höhn et al, 2008). In contrast to other factors like pH and clay, OC varied significantly between land use types (Table 1).…”
Section: Amorphous Silica and Organic Carbonmentioning
confidence: 99%
“…All dried plant and faeces samples (2.0 g) from the summer campaign were shaken thoroughly for 16 h with 20 ml 0.01 M CaCl 2 solution in a 35 ml tube at 208C [25,38]. Extracted samples were then centrifuged at 4000 r.p.m.…”
mentioning
confidence: 99%
“…Kaczorek and Sommer (2004) have shown that under the conditions of soil acidification, the amount of free silica increases. Similarly, Höhn et al (2008) reported an increase in the amount of silicon available in the soil with a decrease in pH. According to Miles et al (2014) where a large group of soils in a region of a country is surveyed, there is generally a positive relationship between pH and Si solubility/extractability.…”
Section: Resultsmentioning
confidence: 99%